Fidelidade de habitat de botos-cinza (sotalia guianensis) em uma área marinha protegida no Nordeste do Brasil - Silva, Gessica Rafaelly Dantas da (2021)
Guiana dolphin, Sotalia guianensis, is a small cetacean associated with bays, inlets and estuaries, which is currently threatened with extinction throughout the national territory. Population information about this species is still rare or inaccurate for many regions and has made it difficult to understand its conservation status, internationally. In order to contribute with population information and support strategies for the conservation of Guiana dolphins, this study investigated: the site-fidelity of Guiana dolphins in the Tibau do Sul Coastal Wildlife Reserve and the use of this protected area as a possible nursery area. In this study, we used photoidentification data, obtained from 2013 to 2019, during 84 days of data collection, totaling seven years of sampling. The photos of dorsal fin of Guiana dolphins were taken with a photographic camera coupled to a 150-600 mm telescopic lens and a monopod, from an elevated strip on the beach, to avoid behavioral changes in these animals. Of a total of 45 photoidentified Guiana dolphins, 10 Guiana dolphins had intermediate site-fidelity and 2 Guiana dolphins had high site-fidelity, Guiana dolphins were considered potential residents, being registered in three or more years of sampling, while another 33 Guiana dolphins were considered occasional visitors, registered in only one or two years of sampling. We photoidentified 17 Guiana dolphins in the company of calves. Groups of Guiana dolphins had an average size (± SE) of 2.4 ± 0.08, ranging from 2 to 5 individuals (n = 98). Calves were present in 35.8% of the records. The Tibau do Sul Coastal Wildlife Reserve has proved to be an important area of concentration and parental care for Guiana dolphins in Brazil, requiring urgent measures to ensure its conservation, in a current scenario of intense tourist exploitation